2007
DOI: 10.1177/1363461507077728
|View full text |Cite
|
Sign up to set email alerts
|

Initiation Rites as a Perceived Stressor for Isixhosa Males with Schizophrenia

Abstract: Although traditional initiation forms a pivotal part of Xhosa culture, it may be a stressful life event for the individual. In this study, 75 Xhosa males diagnosed with schizophrenia were interviewed to examine their perceptions of the role of initiation in the onset and course of their illness. In all, eight patients (10.7%) perceived the initiation rites as a stressful event that had triggered the onset of a psychotic episode, and six (8%) felt it precipitated a relapse. Our findings suggest that initiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The father or family members of the umkhwetha appoint the ikhankatha . Additionally, the village men, who have also undergone the same initiation processes, visit the ibhoma to monitor the healing progress of the wound, teach and prepare umkhwetha for new roles and essential responsibilities towards his family and community members [12]. The umkhwetha is transformed to be a responsible man.…”
Section: Introductionmentioning
confidence: 99%
“…The father or family members of the umkhwetha appoint the ikhankatha . Additionally, the village men, who have also undergone the same initiation processes, visit the ibhoma to monitor the healing progress of the wound, teach and prepare umkhwetha for new roles and essential responsibilities towards his family and community members [12]. The umkhwetha is transformed to be a responsible man.…”
Section: Introductionmentioning
confidence: 99%
“…These findings correspond with a claim by Häfner and An der Heiden 17 that schizophrenia is mainly a disease of adolescence and early adulthood, and their findings that the average age at first contact with mental health services is between 25 and 35 of age for both females and males. Similarly, Le Roux et al 18 reported that the mean age of onset of schizophrenia among Xhosa-speaking patients was 23.14, meaning that it ranges between 14 and 51 years. Male participants in the present study largely outnumbered females.…”
Section: Resultsmentioning
confidence: 91%
“…In society, Xhosa men who have not been ritually circumcised, regardless of their age, are known as "boys". The social significance of the ulwaluko process is profound, as Nelson Mandela (1995) discusses in his autobiography, and it has been suggested that failure to perform the ritual may lead to considerable emotional distress, and possibly even psychosis, let alone the stressful consequences of the process itself for those who undergo it (Le Roux et al, 2007;Swartz, 1986Swartz, , 1987Yen & Wilbraham, 2003). Given the physical location of where the ceremonies are undertaken, and the physical privations for the process, not all men with physical disabilities can take part in the process.…”
Section: Men With Disabilities Doing Sexmentioning
confidence: 99%